Gambaran Hasil Pemeriksaan Laringoskopi Fiber Optik pada Pasien Rawat Inap di RSUP. Prof. Dr. R. D. Kandou Periode 2014 -2017 - Monintja, Yosua K. G.; Mengko, Steward K.; Pelealu, Olivia C. P. (e-CliniC, 2019)
Abstract: Flexible fiber-optic laryngoscopy is one of the most common tool to identify abnormalities in larynx and its surrounding structures, biopsy, or to find abnormal tissues, such as polyps on the larynx. One of the advantages of this tool is the presence of a flexible camera that can be manipulated precisely so that it can show the whole vocal cord movement. In addition, the endoscope used in this procedure is made of thin and flexible fiber optic cable, therefore, the patient only experiences slight discomfort when the laryngoscope is inserted that does not require a long time. This study was aimed to describe the results of fiber-optic laryngoscopy (FOL) in hospitalized patients admitted to Prof. Dr. R. D. Kandou Hospital Manado from 2014 to 2017. This was a descriptive retrospective study with a cross sectional design. Based on medical records, respondents were all inpatients who had the results of FOL examination at the Department of ENT-Head and Neck Surgery Prof. Dr. R. D. Kandou Hospital Manado. From 11 samples, the most common pathological features were arytenoid edema (35.71%) and hyperemic (28.58%), with dysphonia (80%) as the most frequent indication for FOL. Conclusion: The most frequent indication of FOL was dysphonia and the most common pathological abnormalities found were edema and hyperemic of arytenoid.Keywords: fiber optic laryngoscopy (FOL)Â Abstrak: Flexible fiber-optic laryngoscopy ialah pemeriksaan yang paling umum untuk mengetahui kelainan laring dan sekitarnya, biopsi, atau melihat jaringan abnormal seperti polip pada bagian laring. Salah satu keuntungan dari alat ini ialah kamera fleksibel yang dapat dimanipulasi secara tepat sehingga dapat menunjukkan gerakan pita suara secara penuh. Selain itu, endoskopi yang digunakan dalam prosedur ini terbuat dari kabel fiber optik yang tipis dan fleksibel, pasien hanya mengalami sedikit tidak nyaman saat alat dimasukkan dan tidak memerlukan waktu yang lama. Penelitian ini bertujuan untuk mengetahui gambaran hasil pemeriksaan fiber-optic laryngoscopy (FOL) pada pasien rawat inap di RSUP Prof. Dr. R. D. Kandou Manado dari tahun 2014 hingga 2017. Jenis penelitian ialah deskriptif retrospektif dengan desain potong lintang. Responden ialah seluruh pasien rawat inap yang memiliki hasil pemeriksaan FOL yang tercantum dalam rekam medik di KSM THT-KL RSUP Prof. Dr. R. D. Kandou Manado. Hasil penelitian memperlihatkan dari 11 sampel didapatkan gambaran patologik yang paling sering ialah aritenoid yang edema (35,71%) dan hiperemis (28,58%) dengan disfonia (80%) sebagai indikasi paling sering untuk pemeriksaan. Simpulan: Pada pemeriksaan FOL, indikasi tersering ialah disfonia dan gambaran patologik tersering didapatkan ialah edema dan hiperemis aritenoid.Kata kunci: laringoskopi fiber optic (FOL)